The angular gyrus in developmental dyslexia: task-specific differences in functional connectivity within posterior cortex. - Pugh, Kenneth R.; Mencl, W. Einar; Shaywitz, Bennett A. (Psychological Science., 2000)
A study was conducted to examine task-specific differences in functional connectivity within posterior cortex. Data were gathered from a sample of 29 dyslexic readers. The results indicate that for dyslexic readers, a disruption in functional connectivity in the language-dominant left hemisphere is restricted to those tasks that make explicit demands on assembly. It is also revealed that functional connectivity was found to be strong for both dyslexic and nonimpaired readers on print tasks that did not require phonological assembly. These findings support the view that neurobiological anomalies in developmental dyslexia are mainly restricted to the phonological-processing domain, and it is proposed that right-hemisphere posterior regions fulfil a compensatory role in mediating phonological performance in dyslexic readers.